Identificación de marcadores microsatelites polimórficos en el genoma de Dioscorea trífida L.f. “sachapapa” - Ramírez y Cols., Roberson (2019)
The main objective of the study was to identify and evaluate polymorphic microsatellite markers present in genomic DNA D. trífida Lf. To modify this was achieved 2X CTAB protocol that yielded genomic DNA good quality with a ratio of 1.78 showing to be acceptable for the amplification and an amount of 186.9 g/ml of the microsatellites, the same way were standardized and polymorphic microsatellite markers amplified with six pairs of primers, whose amplification products varied in the range of 100 to 200 bp. The 6 microsatellites primer pairs showed no nonspecific products, resulting initiators MTI10 MTI3 and more polymorphic polymorphic information content (PIC) of 0.84 and 0.81 respectively. However; the initiator was less polymorphism MTI4 with a PIC of 0.52. There was a slight dependence between the number of different alleles and polymorphic information content (PIC) with a relatively high correlation index (r2 = 0.69). We conclude that the technique of production and purification of genomic DNA from D. trífida L f. is ideal for extracting genomic DNA, also the 6 pairs of microsatellite markers are adequate standard for future work at the molecular level in this species.